2001
DOI: 10.1021/ma001973m
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Biopolymers for Heavy Metal Removal

Abstract: Tunable biopolymers were synthesized for the removal of heavy metals from dilute waste streams. Protein−protein interaction was tailored specifically into tunable, metal-binding biopolymers using elastin-like polypeptides composed of either one or two hexahistidine clusters. These tunable biopolymers retained the functionality of the elastin domain, undergoing a reversible phase transition above the transition temperature. Aggregation could be tuned within a wide range of temperatures by controlling the chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
95
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 21 publications
(39 reference statements)
2
95
2
Order By: Relevance
“…It is possible to isolate glyco-polypeptides using the interaction between the capture molecule and the sugar group [86] (Figure 8). It has also been shown that ELPs fused to an appropriate fusion partner can bind to heavy metals such as mercury [87], arsenic [88] or cadmium [89,90], and facilitate the rapid isolation of these toxic metal contaminants.…”
Section: Applications Of Elp-based Protein Purification-as the Princimentioning
confidence: 99%
“…It is possible to isolate glyco-polypeptides using the interaction between the capture molecule and the sugar group [86] (Figure 8). It has also been shown that ELPs fused to an appropriate fusion partner can bind to heavy metals such as mercury [87], arsenic [88] or cadmium [89,90], and facilitate the rapid isolation of these toxic metal contaminants.…”
Section: Applications Of Elp-based Protein Purification-as the Princimentioning
confidence: 99%
“…9,10 Recently, applications of these protein polymers have been expanded to stimuli-responsive silk-elastin-like protein block copolymers for high-throughput protein assays, [11][12][13] tunable biopolymers for heavy metal removal, 14 and wheat seed storage proteins. 15 For this reason, we may anticipate that a variety of protein polymers with specific physical properties will be produced for diverse purposes in the future.…”
Section: Introductionmentioning
confidence: 99%
“…The use of ELP as a fusion partner is still a work in progress, as the ELP fusion proteins have reduced overall expression and cause reduced cell growth. 29,[94][95][96] However, in 2012, Liu et al 29 developed an approach that incorporated a mini intein self-cleavage domain (that was fused to the target protein) to facilitate affinity tag removal, along with separately expressed ELP that contained a capture domain for the affinity tag (Figure 2). The affinity pair that was used in this purification technique was a naturally occurring cohesion-dockerin (Coh-Doc) from Clostridium thermocellum that mediates Ca 2+ -dependent binding.…”
Section: Advances In Non-chromatographic Methodsmentioning
confidence: 99%